2013
DOI: 10.1002/acr.22013
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Serum Anti–Müllerian Hormone, a Marker for Ovarian Reserve, in Women With Rheumatoid Arthritis

Abstract: Objective. Fertility is reduced in women with rheumatoid arthritis (RA), even before diagnosis. This may be due to a diminished ovarian reserve. The current study examined serum levels of anti-Mü llerian hormone (AMH), the most reliable endocrine marker for ovarian reserve, in early RA patients and the influence of disease activity and methotrexate (MTX) use on AMH concentrations. Methods. Serum AMH levels were measured in 72 women with recent-onset RA ages 18 -42 years and compared to 509 healthy women. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 14 publications
2
45
0
5
Order By: Relevance
“…This is in contrast to animal studies, where MTX has been shown to cause a reduction in the number of primordial follicles (ie, ovarian reserve) and a subsequent loss of ovarian function 33. We have previously shown that short-term MTX use in early RA does not affect ovarian reserve 34. As the women in the current study had been using MTX for several years, our results suggest that long-term use of MTX also does not have a negative effect on ovarian function and fertility.…”
Section: Discussionmentioning
confidence: 59%
“…This is in contrast to animal studies, where MTX has been shown to cause a reduction in the number of primordial follicles (ie, ovarian reserve) and a subsequent loss of ovarian function 33. We have previously shown that short-term MTX use in early RA does not affect ovarian reserve 34. As the women in the current study had been using MTX for several years, our results suggest that long-term use of MTX also does not have a negative effect on ovarian function and fertility.…”
Section: Discussionmentioning
confidence: 59%
“…However, in a prospective cohort study on RA and fertility, prior MTX treatment did not affect TTP [9]. Furthermore, short-term MTX treatment had no impact on the ovarian reserve in patients with RA [13]. Finally, it has been hypothesized that the impaired fertility in patients with RA is a result of a lower intercourse frequency [12].…”
Section: Fertility In Patients With Ramentioning
confidence: 91%
“…To test this hypothesis, the levels of serum anti-Müllerian hormone (AMH) (the most reliable biomarker for ovarian reserve) were tested in 72 premenopausal women (age range 18e42 years) with early RA. No differences were observed between patients with RA and healthy controls, making it unlikely that the observed impaired fertility, already present at time of diagnosis, is related to a diminished ovarian reserve [13]. Personal choices, due to RA-related concerns, have been shown to be at least partially responsible for the smaller family size [8], but it cannot account for the observed impaired fertility.…”
Section: Fertility In Patients With Ramentioning
confidence: 94%
“…For other DMARDs, the dosage of the Anti Müllerian Hormone (AMH) has been proposed in women taking medications to determine drug influence on fertility: no alterations have been described for methotrexate [156], mycophenolate mofetil, cyclosporine and tacrolimus [155].…”
Section: Medicationmentioning
confidence: 99%